2021
DOI: 10.1002/dmrr.3447
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of vitamin D against oxidative stress in diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a microvascular complication of diabetes mellitus. There is much evidence showing that a high level of mitochondrial overproduction of reactive oxygen species in the diabetic retina contributes in modifying cellular signalling and leads to retinal cell damage and finally to the development of DR pathogenesis. In the last few decades, it has been reported that vitamin D is involved in DR pathogenesis. Vitamin D, traditionally known as an essential nutrient crucial in bone metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 191 publications
(241 reference statements)
0
20
0
4
Order By: Relevance
“…Nevertheless, some diabetes patients without these traditional risk factors can likewise develop a retinal damage, suggesting the involvement of other pathogenetic elements [ 70 ]. Preclinical and clinical studies investigated whether nutraceuticals could influence the course of DR [ 23 , 24 ]. Moreover, diabetes itself can alter the nutritional status, suggesting an attitude to deficiency of micronutrients in diabetes patients [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some diabetes patients without these traditional risk factors can likewise develop a retinal damage, suggesting the involvement of other pathogenetic elements [ 70 ]. Preclinical and clinical studies investigated whether nutraceuticals could influence the course of DR [ 23 , 24 ]. Moreover, diabetes itself can alter the nutritional status, suggesting an attitude to deficiency of micronutrients in diabetes patients [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among modifiable risk factors, unhealthy lifestyles, such as dietary intake, physical activity, tobacco consumption could influence the course of DR [ 21 , 22 ]. In particular, preclinical and clinical studies indicated a possible role of vitamins and micro- or macro-nutrients intake—through usual feeding or dietary supplementation—in the course of DR and its therapy [ 23 , 24 ]. However, current evidence is heterogeneous and controversial, raising the need for a deep evaluation of the role of nutrients and nutraceuticals in DR. For this reason, we carried out a systematic review of both observational and interventional studies, which evaluated the effect of nutrients and/or nutraceuticals on the risk of DR and their potential use for the treatment of patients with DR.…”
Section: Introductionmentioning
confidence: 99%
“…This receptor is expressed in many cells of the immune system including T and B cells, monocytes, neutrophils, macrophages, and dendritic cells ( Zeng et al, 2015 ). It has been demonstrated that GHSR-1A is expressed in alveolar macrophages (AMs) and that Ghre alleviates septic ARDS in rats ( Valle et al, 2021 ) exerting an antiapoptotic effect on AMs. This effect is mediated by GHSR-1A.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DR is a multifactorial condition that is etiopathogenically characterized by hyperglycemia, chronic inflammation, leukostasis, microvascular lesions associated with increased vascular permeability, local ischemia, angiogenesis and neurodegeneration [ 6 ].…”
Section: The Role Of Vitamin D In the Prevention Of Diabetic Retinopathymentioning
confidence: 99%